Ischemia-Modified Albumin Levels and Thiol-Disulphide Homeostasis in Diabetic Macular Edema in Patients with Diabetes Mellitus Type 2. (4th May 2021) - Kalayci, Mustafa; Cetinkaya, Ersan; Yigit, Kenan; Sabaner, Mehmet Cem; Duman, Reşat; Balik, Ahmet Rifat; Erel, Özcan
ABSTRACT: Purpose: It was aimed to assess the role of thiol-disulphide homeostasis and ischemia-modified albumin (IMA) level in the development of diabetic macular edema (DME) in patients with diabetes mellitus type 2 (T2DM). Materials and Methods: Sixty-six study patients were divided into two groups. Group I included 43 patients with T2DM and DME, and Group 2 included 23 patients with T2DM without eye involvement. A novel colorimetric method was used to assess thiol-disulphide homeostasis. Between the two groups IMA, total anti-oxidant, and total oxidant levels were measured and compared. Results: In Group 1, total and native thiol levels and disulphide levels were lower compared to Group 2 ( p = .025, p < .001 and p = .013, respectively). Disulphide/native thiol, disulphide/total thiol ratios and native thiol/total thiol were similar between the groups. Total anti-oxidant level (TAL) reduced whereas total oxidant level (TOL) increased in Group 1 compared to Group 2 ( p = .001, p = .002, respectively). Albumin level decreased, whereas IMA level increased in Group 1 compared to Group 2 ( p < .001 for both). Conclusions: The disruption in thiol/disulphide homeostasis, increased IMA and oxidative stress have an impact on the development of diabetic macular edema.